Canadian history : a reader's guide. - Taylor, M. Brook (Martin Brook), 1951-; Owram, Doug, 1947- (ACLS Humanities E-Book (Series), 1994)
The field of Canadian history has changed and expanded greatly in the last ten years. In these two volumes, which replace the Reader's Guide to Canadian History, experts provide a select and critical guide to historical writing about pre- and post-Confederation Canada, with an emphasis on the most recent scholarship. The guides, therefore, provide quick and easy access to essential material in any subject area for students or for readers seeking direction for broadening their understanding of particular periods, themes, or topics.